Emergence of sequence type 11 Klebsiella pneumoniae coproducing NDM-1 and VIM-1 metallo-β-lactamases in a Greek hospital - Papagiannitsis, C C; Malli, E; Florou, Z; Sarrou, S; Hrabak, J; Mantzarlis, K; Zakynthinos, E; Petinaki, E (Diagnostic microbiology and infectious disease, 2017)
Sequence type 11 Klebsiella pneumoniae, coproducing NDM-1 and VIM-1 metallo-β-lactamases, were isolated in a Greek hospital. blaNDM-1 was part of a Tn125 derivative, located on an ~90-kb plasmid similar to the NDM-1-encoding plasmid pB-3002cz. blaVIM-1 was located in an In-e541-like integron, carried on a multireplicon (IncA/C and IncR) plasmid of ~180kb.
Keywords: Microbial Sensitivity Tests; Humans; Carbapenemases; NDM-1; karbapenemy; Klebsiella pneumoniae; mikrobiální testy citlivosti; lidé; Klebsiella Infections; Enterobacteriaceae; bakteriální proteiny; infekce bakteriemi rodu Klebsiella; beta-laktamasy; VIM-1; Řecko; Hospitals; Greece; Carbapenems; nemocnice; Colonization; Bacterial Proteins; beta-Lactamases